Effects of early-life poverty on health and human capital in children and adolescents: analyses of national surveys and birth cohort studies in LMICs. Issue 10336 (30th April 2022) - Victora, Cesar G; Hartwig, Fernando P; Vidaletti, Luis P; Martorell, Reynaldo; Osmond, Clive; Richter, Linda M; Stein, Aryeh D; Barros, Aluisio J D; Adair, Linda S; Barros, Fernando C; Bhargava, Santosh K; Horta, Bernardo L; et al.
Summary: The survival and nutrition of children and, to a lesser extent, adolescents have improved substantially in the past two decades. Improvements have been linked to the delivery of effective biomedical, behavioural, and environmental interventions; however, large disparities exist between and within countries. Using data from 95 national surveys in low-income and middle-income countries (LMICs), we analyse how strongly the health, nutrition, and cognitive development of children and adolescents are related to early-life poverty. Additionally, using data from six large, long-running birth cohorts in LMICs, we show how early-life poverty can have a lasting effect on health and human capital throughout the life course. We emphasise the importance of implementing multisectoral anti-poverty policies and programmes to complement specific health and nutrition interventions delivered at an individual level, particularly at a time when COVID-19 continues to disrupt economic, health, and educational gains achieved in the recent past.